[RETRACTED] Diversity of vegetation, birds, dragonflies and butterflies at coal mining reclamation sites in South Kalimantan, Indonesia - SLAMET ISWORO; POERNA SRI OETARI (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Isworo S, Oetari PS. 2023. Diversity of vegetation, birds, dragonflies and butterflies at coal mining reclamation sites in South Kalimantan, Indonesia. Biodiversitas 24: 5376-5390. Coal mining can help the country's economy, but it can also be detrimental to the environment, especially due to the reduced biodiversity in mining areas. Recovery efforts are therefore needed to reclaim post-coal mining land. The aim of the research is to identify the biodiversity of plants, birds, dragonflies, and butterflies in the coal mining reclamation area in Banjar and Tapin regencies, South Kalimantan Province, Indonesia. A biodiversity survey was conducted on eight sites representing various reclamation conditions and histories. Based on vegetation studies in the reclamation area, 136 species belonging to 101 families were found. Zone TAJ1-4 had the highest diversity index (H') at the tree, stake and sapling strata with the index of 0.96, 1.06 and 1.71, respectively. The highest diversity index at the pole stratum was recorded in the TAJ1-3 zone with 0.6. Zone TAJ5-8 had the highest diversity index at the herbaceous vegetation, with 2.33. The Fabaceae family dominates all observation sites. The species with the highest importance index for the tree stratum was Acacia mangium, the pole stratum was Albizia chinensis, Hevea brasiliensis and Vitex pinnata, the stake stratum was A. chinensis, the sapling stratum was A. mangium, and the herbaceous stratum was Ottochloa nodosa. The Sorensen Similarity Index fell into the low category (10.00% to 57.78%), showing varying directions of vegetation succession. There were 21 birds, 10 dragonflies, and 15 butterflies recorded across the observation sites. According to the IUCN Red List of Threatened Species, no recorded species is listed as protected. The results of this study might be used for the management of post-mining reclamation areas, especially in South Kalimantan.